(untitled) (Zaranie Śląskie, 2024)
The just transition of the Silesian Voivodeship is one of the key challenges of contemporary Poland. The region, historically a centre of heavy industry, is facing the need for profound economic and social changes resulting from the phasing out of the mining sector. This transition must combine the goals of sustainable development with the protection of social rights, ensuring justice for local residents, especially those affected by restructuring. The article analyses the transition processes since the fall of communism, highlighting historical restructurings and contemporary challenges such as environmental degradation and climate change. Strategies to mitigate social impacts are presented, including government programmes and European funds. The creation of new economic sectors such as innovation, services and tourism to replace traditional industries is key.